MEWUJUDKAN PEMBELAJAR SEPANJANG HAYAT: PERAN POAC DALAM TRANSFORMASI MANAJEMEN PENDIDIKAN (STUDY LITERATURE REVIEW) - Nurajizah; Nita Andriani; Supriyanto; Tubagus Habibi; Mutoharoh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategic role of POAC management functions (Planning, Organizing, Actuating, and Controlling) in transforming educational management to realize the vision of lifelong learning. The method employed is a literature review, collecting data from scientific journals, digital e-books, and relevant official documents. The results indicate that the systematic application of POAC enhances the quality of learning, builds an educational ecosystem adaptive to digital technology, and strengthens individual metacognitive abilities. Effective management is found to be the primary foundation for overcoming access inequality and addressing global challenges in the Industry 4.0 and Society 5.0 eras. The conclusion emphasizes that management transformation through the POAC framework is not merely an administrative necessity but a crucial prerequisite for creating a sustainable learning culture responsive to modern changes. Keywords: Educational Management, POAC, Lifelong Learning, Educational Transformation.